Research on the Influence Mechanism of dual-credit Policy on Green Innovation Level of Automobile Enterprises: Moderating Effect Based on Internationalization Depth and Internationalization Breadth - Ning, Jinzi; Tao, Fanqian (International Journal of Global Economics and Management, 2024)
The “dual-credit” policy is a key strategy implemented by the state to promote green mobility, aiming to encourage automakers to make progress in fuel efficiency and new energy technologies through quantitative management of corporate average fuel consumption points and new energy vehicle points. In this paper, we take Chinese listed automobile enterprises as the experimental group, and match the control group from non-automobile enterprises by propensity score matching method, and use double-difference model to test the incentive effect of the dual-credit policy on the improvement of green innovation level of automobile enterprises. The study finds that the “dual-credit” policy significantly improves the green innovation level of automobile enterprises; the internationalization depth and internationalization breadth of enterprises negatively and positively regulate the incentive effect of the “dual-credit” policy on the improvement of the green innovation level of automobile enterprises, respectively; and the analysis of heterogeneity shows that the “dual-credit” policy has a significant impact on the improvement of the green innovation level of automobile enterprises. “Heterogeneity analysis shows that the dual-credit policy has a more significant positive effect on SOEs than on non-SOEs. Based on the empirical analysis of the policy, targeted suggestions for policy improvement are made.